Physiological Measurements and Transcriptome Survey Reveal How Semi-mangrove Clerodendrum inerme Tolerates Saline Adversity - Liang, Minting; Hu, Feng; Xie, Dongsheng; Chen, Zhibin; Zheng, Qingzhi; Xie, Qiyun; Zheng, Feng; Liu, Dongming; Jian, Shuguang; Chen, Hongfeng; Liu, Xuncheng; Wang, Faguo (Frontiers in Plant Science, 2022)
Salinity adversity has been a major environmental stressor for plant growth and reproduction worldwide. Semi-mangrove Clerodendrum inerme, a naturally salt-tolerant plant, can be studied as a successful example to understand the biological mechanism of saline resistance. Since it is a sophisticated and all-round scale process for plants to react to stress, our greenhouse study interpreted the response of C. inerme to salt challenge in the following aspects: morphology, osmotic protectants, ROS production and scavenging, ion homeostasis, photosynthetic efficiency, and transcriptome reprogramming. The results drew an overview picture to illustrate the tolerant performance of C. inerme from salt acclimatization (till medium NaCl level, 0.3 mol/L) to salinity stress (high NaCl level, 0.5 mol/L). The overall evaluation leads to a conclusion that the main survival strategy of C. inerme is globally reshaping metabolic and ion profiles to adapt to saline adversity. These findings uncover the defense mechanism by which C. inerme moderates its development rate to resist the short- and long-term salt adversity, along with rebalancing the energy allocation between growth and stress tolerance.